ANALISIS KESIAPSIAGAAN POLISI KEHUTANAN TERHADAP POTENSI DAN PENCEGAHAN KEBAKARAN HUTAN DI WILAYAH KPH SEMARANG PERUM PERHUTANI DIVISI REGIONAL JAWA TENGAH (Studi Kasus di Bagian Kesatuan Pemangkuan Hutan Penggaron) - Imam Subha Ari Pamungkas; Ida Wahyuni; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Forests are part of an ecosystem that is essential to the balance of nature. Forest fire is circumstances where the forest is engulfed in flames causing damage to forests and forest products that cause harm of economic and environmental value. Based on data from KPH Semarang forest fires report on June - October 2015, the BKPH Penggaron forest area had experienced five forest fires. Forestry police’s role of the forest fire potential and prevention is extremely important to conserve forests. The objective of this study was to determine the behavior of forestry police preparedness to forest fire potential and prevention in KPH Semarang Perum Perhutani Divisi Regional Jawa Tengah. This study was a descriptive qualitative study with indepth interview. The subjects of this research were 4 people as key informants and 3 people as a triangulation informants.The result of this study showed the key informants already known the definition of forest fire, the caused of forest fire, the impact of forest fire, and tools which beneficial to forest fire protection. Attitude of key informants already prepared to faced forest fire and already did forest fire prevention. Availability of forest fire prevention tools in the workplace was still lacking Availability of forest fire prevention and protection training could support the forestry police duties to forest fire prevention and protection. Support of LMDH, Head of HRD department, Asper, and Security coordinator was extremely important to forest fire prevention and protection. Researcher advicing the company to conduct a risk assessment of forest fires and to consider the provision of sufficient fire-fighting facilities.